2022
DOI: 10.1177/08850666211073582
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and Mortality Outcomes Associated with Ondansetron in Critically Ill Patients

Abstract: Background: Ondansetron is a preferred anti-emetic in critical care to treat nausea and vomiting, and has historically been considered a largely safe option. A recent pharmacoepidemiology study reported that ondansetron may be associated with an increased risk for acute kidney injury (AKI). Methods: We interrogated the High-Density Intensive Care (HiDenIC-15) database containing intensive care data for 13 hospitals across Western Pennsylvania between Oct 2008-Dec 2014. AKI was defined using the Kidney Disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Our study shows that early postoperative ondansetron exposure is associated with better survival at 90 days after surgery in patients with postoperative AKI. This finding is similar to that of three other retrospective cohort studies that investigated critically ills patients with AKI and demonstrated that patients who received ondansetron had significantly lower ICU mortality, in-hospital mortality, and 90-day mortality, respectively ( 17 19 ). Additionally, the genes of 5-HT3 receptor were reported to be upregulated in AKI kidneys, and a molecular mechanism study by gene expression signatures demonstrated that the NF-KB and JAK-STAT pathways might be involved in the potential therapeutic effect of ondansetron in critically ill patients complicated by AKI ( 18 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study shows that early postoperative ondansetron exposure is associated with better survival at 90 days after surgery in patients with postoperative AKI. This finding is similar to that of three other retrospective cohort studies that investigated critically ills patients with AKI and demonstrated that patients who received ondansetron had significantly lower ICU mortality, in-hospital mortality, and 90-day mortality, respectively ( 17 19 ). Additionally, the genes of 5-HT3 receptor were reported to be upregulated in AKI kidneys, and a molecular mechanism study by gene expression signatures demonstrated that the NF-KB and JAK-STAT pathways might be involved in the potential therapeutic effect of ondansetron in critically ill patients complicated by AKI ( 18 ).…”
Section: Discussionsupporting
confidence: 89%
“…In a retrospective study of a large COVID-19 patient cohort, the use of no less than 8 mg of ondansetron within 48 h of hospital admission was associated with a reduced risk of 30-day mortality for all hospitalized patients (Hazard ratio: 0.55, 95%CI: 0.42–0.70; P < 0.001) and those admitted to ICU (Hazard ratio: 0.52, 95%CI: 0.31–0.87; P = 0.012) after severe acute respiratory syndrome coronavirus 2 infection ( 16 ). In another retrospective cohort study using a large multicenter ICU database, ondansetron received within 24 h after ICU admission was associated with a 5.48% decrease (95%CI: −6.17–−4.79; P < 0.001) of 90-day mortality in the regression analysis of the propensity score–matched cohort ( 17 ). Additionally, this association was not seen by other anti-emetics including prochlorperazine and metoclopramide, suggesting that the beneficial effect of ondansetron on survival might be related to effects other than anti-emetic ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the comparison of gene expression signatures, the latest study illustrated that the advantageous effect of OND might be elicited through the NF-KB pathway and JAK-STAT pathway [ 6 , 7 ]. A recent pharmacoepidemiology study reported that OND was also associated with a significant decrease in 90-day mortality on the High-Density Intensive Care (HiDenIC-15) database containing intensive care data for 13 hospitals across Western Pennsylvania [ 17 ]. Last but not least, OND would inhibit agonist-induced platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%